Parates, esperas y negociaciones - Luna Rodríguez, Lourdes Rocío (2025)
In this paper, I am interested in reflecting on the different methodological challenges I went through during the ethnographic work that supports my doctoral thesis (FFyH-UNC). During four years —in non-consecutive periods— I traveled to the province of Jujuy, in Argentina, more precisely to the department of Rinconada located in the Puna region, to investigate the way in which a mining company —of foreign capitals and open-pit operation— builds and guarantees the social license necessary to operate, in relation to fourteen indigenous communities that inhabit the territory where the mining facilities are deployed. During the beginning of this work, some situations took place that seemed to hinder and condition the entry into the field. Throughout this paper, I intend to show how these situations became key elements in the production of anthropological knowledge, while allowing me to question certain methodological disciplinary prejudices usual in the study of elites or powerful groups.